sUAV Technology Introduction to Junior High School Students and Teachers: A Hands-On Workshop - Patrick Lingga; Rafie Djajasoepena; Afrigh Elena Shabra; Iwan Setiawan; Abdullah Maindratama; Dudy Gustiza; Novan Hardana; Muhammad Johan Alibasa; Hatim Gazali; Wandy Wandy (Center for Research and Community Service of Sampoerna University, 2025)
Small Unmanned Aerial Vehicle (sUAV) is operated with no pilot. There has been growing improvements in drones, especially in public security, monitoring, military and disaster operations, traffic surveillance, agriculture, and many more. The purpose of this community service activities was to help junior high school students gain basic knowledge of sUAV and have opportunities to fly basic movements of the drone indoor at low altitude. There were 5 Unmanned Aerial Vehicle (UAV) prepared for this workshop. D-day workshop activities were only 2 hours on 2 October 2025 including preparation at the school. The workshop has been successfully conducted with around 30 participants. Participants had experience to fly indoor sUAVs with the mobile application as the controller and through wireless networks for connectivity, with basic maneuvers (take off/landing, forward/ backward, roll left/right, yaw left/right, and up/down), and took picture in at eye level. Total number of participants was sufficient with the supporting technologies brought to the school.